Annotated record of the detailed examination of Mn deposits from DSDP Leg 63 (Holes 468B, 469, 470, 470A, 471, 472) - Yeats, Robert S; Haq, Bilal U (PANGAEA, 1981)
A primary objective of Leg 63 was to investigate the fluctuations of this eastern boundary current along a north-south transect off the Gulf of California. This information would aid in biostratigraphically correlating open-ocean planktonic zones with local California zonations. Spanning the last 30 m.y., the complicated tectonic history of the continental margin off California and Baja California comprises changes from a subduction zone to a transform boundary and then to an inactive margin. A second objective of Leg 63 was to define and clarify this history using information on sedimentation, unconformities, basement ages, and paleomagnetic reconstructions gained from drilling, in conjunction with geophysical data and pre-existing bottom samples.